Real and Financial Integration in Asia – Recent Evidence and Policy Perspective - Joscha Beckmann; Hans-Jörg Schmerer (Open Economies Review, 2023)
The papers in this Special Issue focus on real and financial integration in Asia. The papers were presented at a workshop organized by the FernUniversität Hagen. We discuss core results and discuss potential policy implications related to monetary policy in China and the integration of Asia in the world economy.
Keywords: F13; F41; E52; 330; Asia; Real and financial integration